A Sociomuseological perspective on Contemporary Dance and Performance in museums and their potential for social and institutional transformation (Cadernos de Sociomuseologia, 2024)
This article examines the entry of performance and contemporary dance into Western museums. Since the 1960s, the performing arts have gradually gained space in museum institutions. Referencing various authors in the fields of Sociomuseology and Dance Studies, this text seeks to provide an understanding of the body as an element that accumulates knowledge transmissible through movement, based on the thoughts of authors such as Maria Leda Martins, Zeca Ligiério, and Susan Leigh Foster, among others. Two case studies will be explored to understand how performance and contemporary dance can relate to the need to decolonize museum spaces: choreographer Amanda Piña and the artist duo Antonio Amador and Jandir Junior. These are examples that offer different artistic perspectives and approaches regarding the possibility of transforming museums.Keywords: Sociomuseology; Contemporary Dance; Performance; Decolonial; Art Museums.